Taking Restitution Seriously? Victim-Oriented Gaps in the Criminal Justice System - Indra Ardiansyah; Anis Widyawati; Indah Sri Utari; Moh. Fadhil (IJCLS (Indonesian Journal of Criminal Law Studies), 2025)
In cases of sexual violence, child victims have the right to seek restitution in alignment with their best interests. Although this right is enshrined in various regulations, in practice, victims face significant challenges in accessing it. For example, at the Kaimana District Court, out of 61 cases, only 1 case successfully accessed restitution. A critical examination of the obstacles faced by law enforcement officials in institutionalizing victim restitution is essential to bridging the gap between victims and the criminal justice system. This article explores the findings related to the failure of law enforcement officials to provide access to justice for victims of sexual violence at the Kaimana District Court. The research employs a qualitative approach, utilizing data collected through field research techniques such as in-depth interviews with judges, documentation review, and a literature study. Secondary legal materials are also analyzed to provide context to the findings. The study reveals that the failure to implement restitution at the Kaimana District Court stems from the prevailing paradigm within the criminal justice system, which prioritizes the retribution of the accused over the needs and rights of the victim. Another institutional challenge is the inaccessibility of the LPSK which is difficult for victims to reach. To address these issues, it is crucial to enhance the role of professional social workers in regional offices, who act as subordinates of the LPSK. Furthermore, the proactive involvement of judges in court is necessary to ensure the effective application of Regulation of the Supreme Court on Restitution.